2013
DOI: 10.1016/j.ymben.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of xylose utilization for high yield production of lactate-enriched P(lactate-co-3-hydroxybutyrate) using a lactate-overproducing strain of Escherichia coli and an evolved lactate-polymerizing enzyme

Abstract: produced a copolymer having a higher LA fraction (34 mol%) than that grown on 6 glucose (26 mol%). This benefit of xylose was further enhanced by combining it with 7 an evolved LPE (ST/FS/QK), achieving a copolymer production having 60 mol% LA 8 from xylose, while glucose gave a 47 mol% LA under the same condition. The overall 9 carbon yields from the sugars to the polymer were similar for xylose and glucose, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…This indicates that constitutive expression might not always be sufficient, and that additional optimization steps maybe required to engineer new metabolic pathways. Based on this and many other studies (Nduko et al, 2013;Utrilla et al, 2012;Zhou et al, 2012), one such step is evolutionary engineering. Genome sequencing is another, it being a powerful tool to characterize desirable phenotypes and provide a template for reverse engineering.…”
Section: Xylitol Production By Fed-batch Fermentationmentioning
confidence: 92%
“…This indicates that constitutive expression might not always be sufficient, and that additional optimization steps maybe required to engineer new metabolic pathways. Based on this and many other studies (Nduko et al, 2013;Utrilla et al, 2012;Zhou et al, 2012), one such step is evolutionary engineering. Genome sequencing is another, it being a powerful tool to characterize desirable phenotypes and provide a template for reverse engineering.…”
Section: Xylitol Production By Fed-batch Fermentationmentioning
confidence: 92%
“…In a 2013 study, the application of xylose for the production of P(LA-co-3HB) was reported for the first time (35). The advantage of using of xylose for the production of P(LA-co-3HB) was justified by the higher cellular polymer content and LA fraction of the copolymer compared to the utilization of glucose.…”
Section: Xylose Use For the Production Of P(la-co-3hb)mentioning
confidence: 99%
“…In earlier studies using glucose, copolymers with LA fraction greater than 50 mol% were characterized with low polymer yields (less than 1 g/L) from 20 g/L glucose, limiting exploration of polymer properties (25). However, when using xylose, 7.3 g/L of P(60 mol% LA-co-3HB) was obtained, demonstrating the dual advantage of using xylose (35). To exploit the advantage of xylose, two distinct strategies were explored to improve LA fractions and polymer yields (36).…”
Section: Xylose Use For the Production Of P(la-co-3hb)mentioning
confidence: 99%
See 1 more Smart Citation
“…D-Xylose is one of the main hydrolysis products of lignocellulosic biomass and is the second most abundant fermentable material. In contrast to the efficient glucose fermentation in yeast, xylose fermentation is challenging because only a few ethanolproducing microorganisms can readily ferment xylose, even though many microorganisms utilize xylose as a carbon source (Hu et al, 2011;Nduko et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%